Addressing enablers in layers of protection analysis. Issue 3 (22nd January 2014) - Baybutt, Paul
<x xml:space="preserve">Abstract</x> Layers of protection analysis (LOPA) is used to evaluate the risk of individual hazard scenarios by combining initiating event frequencies with failure probabilities of protection layers. Some practitioners include events and conditions that enable the occurrence of hazard scenarios in the analysis, such as conditional modifiers, but sometimes they are excluded to ensure conservative results. However, these events and conditions, and other factors that enable scenarios, are often key parts of hazard scenarios and their exclusion from the analysis can result in overly conservative results. This article broadens the definition of enabling events and conditions to include other factors that can have a significant impact on the risk of hazard scenarios. Such other factors include management systems to account for inadequacies in, and failure to follow, policies, procedures, and work instructions; at‐risk factors to account for the time period in which a process is at risk; incident outcomes to represent different possible consequences for the same initiating event; and release conditions to account for different release conditions or circumstances. Their inclusion in LOPA studies is described with examples. The determination of adjustment factors to account for their effect on scenario risk is also demonstrated. © 2014 American Institute of Chemical Engineers Process Saf Prog 33: 221–226, 2014